Once upon a time. The complete sixth season [videorecording (DVD)] - Kitsis, Eddy; Horowitz, Adam, 1971- (Once upon a time., 2017)
After Regina crushes the heart of her Dark Half, it appears Storybrooke will finally enjoy an era of tranquility. But this reprieve is short-lived when the Evil Queen reemerges and wreaks a level of havoc and terror that makes her previous cruelties pale by comparison. Desperate to right her counterpart's wrongs, Regina fights the ultimate battle against her nemesis, but can one survive if the other is destroyed?